Socialization of Legal Protection of Children Against the Law - Muhammad Bahir (Khidmatuna (Jurnal Pengabdian Kepada Masyarakat), 2023)
Protection of children who are in conflict with the law in the juvenile criminal justice process at every stage starting from investigation, prosecution and trial to juvenile correctional institutions has not been able to provide protection that can provide a sense of justice for children and even children's rights are often neglected. So far, children are often positioned as objects and tend to harm children. In child cases, sometimes children are perpetrators, victims and witnesses, so they need serious protection and handling to anticipate this so that it does not have a wider impact and harm children, such as in the cases of Mario Dandi and Agnes. The handling of child cases must be carried out by officials who really understand children's problems. In Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. Protection of children in conflict with the law is progressing with a paradigm shift in handling cases of children in conflict with the law, the process of resolving child cases can not only be resolved through the judicial process but can also be resolved outside the judicial process through diversion with a restorative justice approach involving all both the perpetrators, victims and witnesses with other related parties to sit together to find solutions for resolving child cases in the best interest of the child.